Antifungal and anti-biofilm activity of a new Spanish extract of propolis against Candida glabrata - María Coronada Fernández-Calderón; Laura Hernández-González; Carolina Gómez-Navia; María Teresa Blanco-Blanco; Rosa Sánchez-Silos; Leopoldo Lucio; Ciro Pérez-Giraldo (BMC, 2021)
Abstract Background Resistance to traditional antifungal agents is a considerable health problem nowadays, aggravated by infectious processes related to biofilm formation, usually on implantable devices. Therefore, it is necessary to identify new antimicrobial molecules, such as natural products, to develop new therapeutic strategies to prevent and eradicate these infections. One promising product is propolis, a natural resin produced by honeybees with substances from various botanical sources, beeswax and salivary enzymes. The aim of this work was to study the effect of a new Spanish ethanolic extract of propolis (SEEP) on growth, cell surface hydrophobicity, adherence and biofilm formation of Candida glabrata, a yeast capable of achieving high levels of resistance to available anti-fungal agents. Methods The antifungal activity of SEEP was evaluated in the planktonic cells of 12 clinical isolates of C. glabrata. The minimum inhibitory concentration (MIC) of propolis was determined by quantifying visible growth inhibition by serial plate dilutions. The minimum fungicide concentration (MFC) was evaluated as the lowest concentration of propolis that produced a 95% decrease in cfu/mL, and is presented as MFC50 and MFC90, which corresponds to the minimum concentrations at which 50 and 90% of the C. glabrata isolates were inhibited, respectively. Influence on cell surface hydrophobicity (CSH) was determined by the method of microbial adhesion to hydrocarbons (MATH). The propolis effect on adhesion and biofilm formation was determined in microtiter plates by measurement of optical density (OD) and metabolic activity (XTT-assay) in the presence of sub-MIC concentrations of SEEP. Results SEEP had antifungal capacity against C. glabrata isolates, with a MIC50 of 0.2% (v/v) and an MFC50 of 0.4%, even in azole-resistant strains. SEEP did not have a clear effect on surface hydrophobicity and adhesion, but an inhibitory effect on biofilm formation was observed at subinhibitory concentrations (0.1 and 0.05%) with a significant decrease in biofilm metabolism. Conclusions The novel Spanish ethanolic extract of propolis shows antifungal activity against C. glabrata, and decreases biofilm formation. These results suggest its possible use in the control of fungal infections associated with biofilms.